CLOX: an executive clock drawing task. Issue 5 (1st May 1998) - Royall, Donald R; Cordes, Jeffrey A; Polk, Marsha
Abstract : OBJECTIVE: To describe a clock drawing task (CLOX) designed to elicit executive impairment and discriminate it from non-executive constructional failure. SUBJECTS: 90 elderly subjects were studied (45 elderly and well persons from the independent living apartments of a continuing care retirement community and 45 patients with probable Alzheimer's disease). The clock drawing performance of elderly patients was compared with that of 62 young adult controls. METHODS: Subjects received the CLOX, an executive test (EXIT25), and the mini mental state examination (MMSE). The CLOX is divided into an unprompted task that is sensitive to executive control (CLOX1) and a copied version that is not (CLOX2). Between rater reliability (27 subjects) was high for both subtests. RESULTS: In elderly subjects, CLOX subscores correlated strongly with cognitive severity (CLOX1: r =−0.83 v the EXIT25; CLOX2: r =0.85 v the MMSE). EXIT25 and MMSE scores predicted CLOX1 scores independently of age or education ( F (4, 82)=50.7, p<0.001; R 2 =0.71). The EXIT25 accounted for 68% of CLOX1 variance. Only the MMSE significantly contributed to CLOX2 scores ( F (4, 72)= 57.2, p<0.001; R 2 =0.74). CLOX subscales discriminated between patients with Alzheimer's disease and elderly controls (83.1% of cases correctly classified; Wilkes' lambda=0.48, p<0.001), and between Alzheimer's disease subgroups with and without constructional impairment (91.9% of cases correctly classified; Wilkes' lambda=0.31, p<0.001). CONCLUSIONS: The CLOX is an internally consistent measure that is easy to administer and displays good inter-rater reliability. It is strongly associated with cognitive test scores. The pattern of CLOX failures may discriminate clinical dementia subgroups.